2016
DOI: 10.1002/aenm.201502555
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal Disulfides as Noble‐Metal‐Alternative Co‐Catalysts for Solar Hydrogen Production

Abstract: The production of hydrogen fuels by using sunlight is an attractive and sustainable solution to the global energy and environmental problems. Platinum (Pt) is known as the most efficient co‐catalyst in hydrogen evolution reaction (HER). However, due to its high‐cost and limited‐reserves, it is highly demanded to explore alternative non‐precious metal co‐catalysts with low‐cost and high efficiency. Transition metal disulfides (TMDs) including molybdenum disulfide and tungsten disulfide have been regarded as pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
139
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 298 publications
(140 citation statements)
references
References 117 publications
(156 reference statements)
1
139
0
Order By: Relevance
“…[40] Semiconducting TMDCsh ave also been reported to exhibit promising behavior for serving as co-catalysts for TiO 2 nanostructures owing to their low-costa nd abundance in nature. [41,42] In addition, theoretical calculations have indicated that the Gibbs free energy of adsorbed atomic hydrogen for TMDCs is close to zero (+ 0.08 Vf or the MoS 2 edge), demonstrating their potentialf or H 2 evolution reaction. [43] TMDCsasp hotosensitizer for improving photocatalytic activity of TiO 2 nanostructures Considering that TiO 2 can only absorb the UV portion of solar spectrum,i ti sh ighly crucial to enhance the photocatalytic efficiencyo fT iO 2 -based photocatalysts by extending their lightharvesting window to the visible light range using TMDC nanosheets due to their relatively narrow band gap.…”
Section: Hydrogen Evolution Reaction On Tmdc/tio 2 Nanocompositesmentioning
confidence: 99%
“…[40] Semiconducting TMDCsh ave also been reported to exhibit promising behavior for serving as co-catalysts for TiO 2 nanostructures owing to their low-costa nd abundance in nature. [41,42] In addition, theoretical calculations have indicated that the Gibbs free energy of adsorbed atomic hydrogen for TMDCs is close to zero (+ 0.08 Vf or the MoS 2 edge), demonstrating their potentialf or H 2 evolution reaction. [43] TMDCsasp hotosensitizer for improving photocatalytic activity of TiO 2 nanostructures Considering that TiO 2 can only absorb the UV portion of solar spectrum,i ti sh ighly crucial to enhance the photocatalytic efficiencyo fT iO 2 -based photocatalysts by extending their lightharvesting window to the visible light range using TMDC nanosheets due to their relatively narrow band gap.…”
Section: Hydrogen Evolution Reaction On Tmdc/tio 2 Nanocompositesmentioning
confidence: 99%
“…J absorbed depends on the intrinsic light absorption range of the photocatalyst and can be improved easily, whereas the strategy to enhance η separation is difficult and restricted . This can be ascribed to the fact that most photocatalysts cannot provide an active site for hydrogen reduction on the surface, resulting in the facile recombination of photogenerated electrons and holes before transferring to the surface for oxidation and reduction reactions . Therefore, activating the surface sites to decrease the activation energy is critical for hydrogen evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, transition metal sulfides, such as NiS, MoS 2, and WS 2 have been demonstrated as effective catalyst alternatives to noble metals (e.g., Ag, Pt, and Pd) . WS 2 is promoting semiconductor as an adjustable bandgap photocatalyst that can be more effective than TiO 2, an archetypal photocatalytic matter.…”
Section: Introductionmentioning
confidence: 99%